(untitled) (Archives of Pediatrics of Uruguay, 2026)
Introduction: typhoid fever (TF), caused by salmonella enterica serovar typhi, remains a significant disease in endemic regions, despite advances in prevention and treatment. Although its overall incidence has decreased, it still primarily affects children and adolescents, especially in areas with poor sanitation. Objectives: to describe the diagnostic and therapeutic approach to a clinical case. Clinical case: a 5-year-old girl presented with fever during 5 days, weakness, headache, abdominal pain, and vomiting, which was initially interpreted as a probable urinary tract infection (UTI). The diagnosis was confirmed by isolation of Salmonella spp. in blood culture; serotyping was S. Typhi. Her mother presented fever and headache, with isolation of S. Typhi in 2 blood cultures. Both cases progressed favorably. The patient had no known contact with patients or carriers of TF, or possible contaminated food. Discussion: timely diagnosis and antibiotic treatment are key to avoiding serious complications and the spread of the disease.Primary prevention plays a fundamental role in reducing its incidence. In Uruguay, it is important to consider TF among the differential diagnoses of acute febrile illnesses with nonspecific or atypical presentation and a secondary familial case of TF.